A global synthesis of human impacts on the multifunctionality of streams and rivers. (17th May 2022) - Brauns, Mario; Allen, Daniel C.; Boëchat, Iola G.; Cross, Wyatt F.; Ferreira, Verónica; Graeber, Daniel; Patrick, Christopher J.; Peipoch, Marc; von Schiller, Daniel; Gücker, Björn
Abstract: Human impacts, particularly nutrient pollution and land‐use change, have caused significant declines in the quality and quantity of freshwater resources. Most global assessments have concentrated on species diversity and composition, but effects on the multifunctionality of streams and rivers remain unclear. Here, we analyse the most comprehensive compilation of stream ecosystem functions to date to provide an overview of the responses of nutrient uptake, leaf litter decomposition, ecosystem productivity, and food web complexity to six globally pervasive human stressors. We show that human stressors inhibited ecosystem functioning for most stressor‐function pairs. Nitrate uptake efficiency was most affected and was inhibited by 347% due to agriculture. However, concomitant negative and positive effects were common even within a given stressor‐function pair. Some part of this variability in effect direction could be explained by the structural heterogeneity of the landscape and latitudinal position of the streams. Ranking human stressors by their absolute effects on ecosystem multifunctionality revealed significant effects for all studied stressors, with wastewater effluents (194%), agriculture (148%), and urban land use (137%) having the strongest effects. Our results demonstrate that we are at risk of losing the functional backbone of streams and rivers if human stressors persist in contemporary intensity, and that freshwaters are losing critical ecosystem services that humans rely on. We advocate for more studies on the effects of multiple stressors on ecosystem multifunctionality to improve the functional understanding of human impacts. Finally, freshwater management must shift its focus toward an ecological function‐based approach and needs to develop strategies for maintaining or restoring ecosystem functioning of streams and rivers. Abstract : Human stressors have caused significant declines in the quality and quantity of freshwater resources, but effects on the multifunctionality of streams and rivers remain unclear. We used meta‐analyses to quantify the responses of nutrient uptake, leaf litter decomposition, ecosystem productivity, and food web complexity to six human stressors. Stressors mostly inhibited ecosystem functioning, and nitrate uptake was most strongly affected. Wastewater effluents, agriculture, and urban land use had the strongest absolute effects on ecosystem multifunctionality. If such stressors persist in contemporary intensity, we will lose the functional backbone of streams and rivers and ecosystem services essential to humans.